2006
DOI: 10.1111/j.1574-6968.1997.tb10304.x
|View full text |Cite
|
Sign up to set email alerts
|

Induction of aldose reductase and xylitol dehydrogenase activities in Candida tenuis CBS 4435

Abstract: In this study the ability of various sugars and sugar alcohols to induce aldose reductase (xylose reductase) and xylitol dehydrogenase (xylulose reductase) activities in the yeast Candida tenuis was investigated. Both enzyme activities were induced when the organism was grown on D-xylose or L-arabinose as well as on the structurally related sugars D-arabinose or D-lyxose. Mixtures of D-xylose with the more rapidly metabolizable sugar D-glucose resulted in a decrease in the levels of both enzymes formed. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(10 citation statements)
references
References 18 publications
1
8
0
1
Order By: Relevance
“…It is likely that the yeast growth on D-xylose or xylitol was limited by the transport of these carbon sources across the cell membrane, or by their successive conversion to xylulose-5-phosphate, thus reaching cell concentrations comparable to that on glucose (9.48 ± 0.11 g DW l -1 ). Similarly, Candida tenuis CBS 4435 showed the highest biomass production on hexoses, whereas the growth on xylose became very effective after 24 h of cultivation [8], thus proving the effectiveness of xylose metabolism in this yeast. Figure 1b shows the effect of the different carbon sources on the specific growth rate (l) of D. hansenii UFV-170.…”
Section: Fermentations In Semi-synthetic Mediamentioning
confidence: 89%
See 3 more Smart Citations
“…It is likely that the yeast growth on D-xylose or xylitol was limited by the transport of these carbon sources across the cell membrane, or by their successive conversion to xylulose-5-phosphate, thus reaching cell concentrations comparable to that on glucose (9.48 ± 0.11 g DW l -1 ). Similarly, Candida tenuis CBS 4435 showed the highest biomass production on hexoses, whereas the growth on xylose became very effective after 24 h of cultivation [8], thus proving the effectiveness of xylose metabolism in this yeast. Figure 1b shows the effect of the different carbon sources on the specific growth rate (l) of D. hansenii UFV-170.…”
Section: Fermentations In Semi-synthetic Mediamentioning
confidence: 89%
“…Several works showed that the expression of the XR gene is subject to regulation by induction and catabolite repression [8,[16][17][18][19]. D-Xylose is reported to be the best XR gene inducer, followed closely by L-arabinose [8,[18][19][20], which suggests that in general pentoses can be effective in the induction of XR gene.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…As hemiceluloses podem ser classificadas como xilanas, mananas, arabinoxilanas, arabinogalactanas e arabinanas BIELY, 1985;KERN et al, 1997;AGUIAR et al, 1999). A xilana é hidrolisada em açúcares monômeros constituintes (glicose, xilose, arabinose, galactose, manose e outros oligossacarídeos) usando ácido diluído, álcali, explosão a vapor, explosão com amônio (AFEX) (HOLTZAPPLE et al, 1991) ou uma mistura de tratamentos enzimaticos (amilase, xilanase e celulase) (HESPELL et al, 1997, SAHA et al).…”
Section: Residuos Lignocelulosicosunclassified